Hubungan antara Kualitas Tidur dengan Konsentrasi Belajar pada Mahasiswa Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra - Sukamto, Inayah Syahputri; Jayanthi, Sri; Nursamsu, Nursamsu (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
Learning concentration is focusing attention and thoughts on something. Learning concentration can be influenced by physical, spiritual factors and lack of sleep. Poor sleep quality is commonly found among university students which can affect study concentration. This study aims to determine sleep quality, study concentration and the relationship between sleep quality and study concentration of Biology Education students at Samudra University. This research used descriptive quantitative method with observation design. The research population was Biology Education students of batch 2023, 2022, 2021 with a sample of 32 students. Data analysis used chi square test. The results showed that there were 17 (53%) had poor sleep quality. The majority of students' learning concentration in the morning is good 18 (56%), while in the afternoon the majority is less 19 (59%). Chi Square test in the morning (p 0.004) with a contigency coefficient of 0.499 and in the afternoon (p 0.014) with a contigency coefficient of 0.446 means that there is a relationship between sleep quality and study concentration of Biology Education students at Samudra University with moderate relationship strength.